A method of monitoring the functional surfaces of the micro-opto-electro-mechanical systems’ components - І.Ш. Невлюдов; О.І. Филипенко; О.О. Чала; І.В. Боцман (Наука і техніка Повітряних Сил Збройних Сил України)
The article presents a method of control of functional surfaces of MOEMS elements of special purpose, which can be used in the technology of production of such structures. This method of non-destructive testing allows to obtain information about the parameters of the topology of the surface of functional structures, by eliminating the accompanying components in the interference signal. The method, in comparison with others, allows to increase the reliability of technological operations of production of functional surfaces of optical signal switches by more than 20% and to reduce labor costs up to 35%. Using the proposed method, it is possible to give recommendations for improving the technological process of manufacturing MOEMS functional surfaces, to ensure the specified values of their topology. The modeling by means of computer processing is performed in the paper in order to determine the extremes of the bands of interference images of the functional surfaces of MOEMS elements.